Tinjauan Mekanisme dan Praktik Pengelolaan Dana Perhitungan Fihak Ketiga (PFK) Pegawai oleh Bendahara Umum Negara: Review of Mechanisms and Practices for Management of Employee Third Party Calculation Funds (PFK) by the State General Treasurer - Achmat Subekan; Rudy Widodo (AMANAH: Jurnal Manajemen Keuangan Sektor Publik, 2026)
The management of Employee Third-Party Funds (PFK) constitutes an integral part of the state treasury system under the authority of the Minister of Finance acting as the State General Treasurer (BUN). The complexity of the mechanisms for collection, reconciliation, disbursement, and accountability of these funds makes their management important to examine from both regulatory and administrative practice perspectives. This study aims to analyze the mechanisms and practices of managing Employee PFK implemented by the State General Treasurer. This research employs a qualitative approach using a descriptive-analytical method, conducted through regulatory review, document analysis, and interviews. The findings indicate that the management of Employee PFK by the BUN has been carried out in accordance with prevailing laws and regulations. The mechanisms for collecting and distributing funds involve multiple stakeholders, including local governments, ministerial/institutional working units, social security administering bodies, as well as supervisory and audit institutions. The reconciliation and accountability processes are conducted in stages to ensure data accuracy and the accountability of financial reporting. Overall, the involved parties have performed their duties and roles effectively and efficiently within the framework of the state financial control system.